Impact of Intraoperative Degrees of Hypotensive Anaesthesia Using Dexmedetomidine on Perioperative Renal Injuries in Patients Undergoing Endoscopic Sinus Surgery - Mohammed Mohammed; Mostafa Abdelsalam; Mona Tawfik; Mona Mostafa; Zenat Mohammed (International Journal of Medical Arts, 2023)
Background and objective: Although controlled intraoperative hypotension is essential in functional endoscopic sinus surgery [FESS], it could lead to vital organ hypoperfusion. Herein, we evaluated the effects of maintaining mean blood pressure [BP] around 60 mmHg on renal function compared to its maintenance around 70 mmHg.Patients and Methods: We included 134 patients undergoing FESS procedure in this randomized prospective trial. Patients were divided into two groups; mean BP was kept around 70 mmHg in group A participants, while the same parameter was kept around 60 mmHg in group B patients. Preoperative and intraoperative kidney function were evaluated by the resistive index.Results: Most preoperative parameters were statistically comparable between the two groups. Group B patients had better surgical field quality. The incidence of acute kidney injury [AKI] was 9% and 20.9% in Groups A and B, respectively [p = 0.052]. However, the intraoperative resistive index showed a marked increase in Group B [0.81 vs. 0.75 in Group A]. High baseline creatinine and a high intraoperative resistive index were independent predictors for AKI. High postoperative serum creatinine was also a significant risk factor.Conclusion: A high preoperative creatinine and intraoperative resistive index are strong risk factors for AKI.